EFFECT OF DRILLING PARAMETERS ON THRUST FORCE AND DELAMINATION DAMAGE OF DRILLED RAMIE WOVEN – COIR FIBER HYBRID COMPOSITES - Chandrabakty, Sri; Fadly, Muhammad Syaiful; Nilasari, Sri (Jurnal Rekayasa Mesin, 2024)
This study examines the effect of spindle speed and feed rate variations on the delamination mechanism and thrust force of hybrid composite materials reinforced with ramie weave and coir fibers. The specimen was made with a volume fraction of 30%, consisting of 6 layers of woven ramie, with the remainder being coir. The drilling process is divided into four main phases, showing changes in thrust force at each stage. The results indicate that an increase in feed rate tends to increase thrust force and cause microstructural damage such as delamination and fiber pull-out. At a feed rate of 0.26 mm/rev and a spindle speed of 1500 RPM, the maximum thrust force is reached, indicating the most severe damage. The delamination factor is higher on the exit side compared to the entry side, especially at higher spindle speeds. Tensile tests show a significant decrease in the tensile strength of the composite material due to drilling, with the highest tensile stress achieved at a spindle speed of 1500 RPM and a feed rate of 0.1 mm/rev, although still lower than the sample without holes. The combination of high feed rate and high spindle speed increases the risk of material damage, but the proper selection of drilling parameters can help minimize damage and maintain the mechanical integrity of the composite material. This study provides important insights for industrial applications where mechanical strength and drilling efficiency are crucial.